DINAMIKA KOPISODA: STUDI TENTANG AKTIVITAS DAN PEMIKIRAN KH SHOLEH DARAT - Mustaqim, Abdul; Adam, Mohammed; Habib, Habib; Ni’am, Mohammad Fattahun (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
Amid rapid modernization, KOPISODA (Komunitas Pencinta Kiai Sholeh Darat) has emerged as a community dedicated to reviving and preserving the intellectual legacy of a prominent Islamic scholar KH Sholeh Darat. This study explores the dynamics of KOPISODA's activities across Semarang, Yogyakarta, and Klaten, focusing on three core questions: (1) What is the historical trajectory of KOPISODA's development? (2) What factors have contributed to its continuity? (3) What are its contributions to Islamic thought in Indonesia? Employing a qualitative method with historical and phenomenological approaches, data were collected through observation, interviews, documentation, and other relevant sources. Findings indicate that KOPISODA has evolved from a social gathering group into a research-oriented community. This transformation is reflected in its efforts to collect, preserve, digitize, translate, and publish KH Sholeh Darat’s works. The community’s sustainability is supported by the enduring influence of KH Sholeh Darat, the dedication of its founders, backing from his descendants, and the sustained commitment of its members. KOPISODA’s initiatives have not only preserved Javanese-Islamic traditions but have also contributed to the transmission and transformation of moderate Islamic knowledge that harmonizes religious values with national identity.